Evaluation of a Virtual Reality-Based Introduction to Hazardous and Toxic Waste Management Using the Technology Acceptance Model - Rananda Saputra, Denaldi; Tranggono, Tranggono; Annisa Islami, Mega Cattleya Prameswari (Journal of Applied Informatics and Computing, 2025)
The management of hazardous and toxic waste (B3 waste) demands innovative educational approaches to improve technical comprehension and environmental awareness, particularly among internship students. This study presents a formative evaluation of an early-stage virtual reality (VR) application prototype, aimed at assessing initial user perceptions and gathering feedback to guide further development, using the Technology Acceptance Model (TAM) framework. The prototype was tested on six internship students involved in the supervision of B3 waste in collaboration with the Environmental Agency (Dinas Lingkungan Hidup) of East Java Province. Data were collected through a questionnaire focusing on three TAM dimensions: Perceived Ease of Use, Perceived Usefulness, and Attitude Toward Technology. The results showed that the VR application was perceived as highly useful (87.5%), easy to use (89.2%), and positively received by users (92.5%). These findings indicate that VR technology holds strong potential as an interactive learning tool for introducing hazardous and toxic waste management practices. The study recommends continued content development and broader testing with a larger respondent base to validate these initial results.